Blood minerals level affecting pregnancy rate in cows and buffaloes - SRIVASTAVA, S K; SAHNI, K L (The Indian Journal of Animal Sciences, 2013)
Plasma protein, inorganic phosphorus and cholesterol were estimated at the time of Al in cows and buffaloes under village and farm conditions. Nondescript cows and buffaloes, 55 each, were included in the study under field condition. Above minerals were also estimated during fertile and non-fertile oestrus in Hariana, Holstein Fresian, Halfbreds (FxH), three-breed cross cows and buffaloes in farm condition. The values during fertile oestruses were higher in cows and buffaloes than non-fertile under village and farm conditions both. Among farm animals, halfbred cows (F x H) had higher values of protein, phosphorus and cholesterol during fertile oestrus than other breed. Significant difference (P<0.05) was observed only in halfbred (FxH) cows between fertile and non-fertile oestrus than other breed and that too in protein and cholesterol Concentration only.